Oral Administration of The Hypercholesterol Rat Feed Formula to Making The Animal Dyslipidemia Model on Sprague Dawley Rats - Fatchiyah Fatchiyah; Eko Suyanto; Rista Nikmatu Rohmah; Lidwina Faraline Triprisila; Hazna Noor Meidinna; Dewi Ratih Tirto Sari; Iva Himmatul Aliyah (Biotropika: Journal of Tropical Biology, 2021)
The aim of this study was to make animal dyslipidemia models in Sprague Dawley strains induced by a high fat goat diet formula as hypercholesterol feed for two months. The experimental animal used in this study was 30 male rats (Rattus norvegicus strain Sprague Dawley) with an age of 2-3 months with an average body weight of 150g. Animal models are divided into two groups consisting of a control group without additional diet and dyslipidemia group given food consumption goat hypercholesterolemia with high-fat diet formula orally every day for two months. Physiological characteristics of dyslipidemia SD rats had higher body weight, increased food consumption and fecal weight, and decreased water intake and urine volume than the control group. Total cholesterol, triglyceride, and LDL-cholesterol levels increased, while HDL-cholesterol levels did not change in the dyslipidemia rats group compared to the control group. The conclusion of this study indicated that the hypercholesterol diet formula with a high composition of goat fat was successfully induced the SD rats to become dyslipidemia model rat with specific hypercholerol characteristics.